Penggunaan Alang-alang untuk Mengendalikan Gulma dan Meningkatkan Produksi Tanaman Jagung (Zea mays L.) di Lahan Kering - Idi Darpan Maulana; M. A. Chodzin (IPB University, 2011)
A field experience conducted at Cikabayan, IPB Dramaga Bogor from January to Juni 2010 was designed to determine the effect of different dosage of ‘alang-alang’ much compared with control such as nno weeding and usual weeding on growth and yield of corn. The experiment was designed in a randomized complete block designed with three replications. The treatment was dosage of ‘alang-alang’ mulch consisting of 0, 2, 4, 6, 8 ton ha -1. Result indicated thar ‘alang-alang’ mulching (6 and 8 ton ha -1) increased plant growth and production. Beside that, ‘alang-alang’ mulching suppressed weed growth.Keywords : alang-alang, mulch, weed, maize